2014
DOI: 10.1002/nme.4707
|View full text |Cite
|
Sign up to set email alerts
|

On the representation and implicit integration of general isotropic elastoplasticity based on a set of mutually orthogonal unit basis tensors

Abstract: SUMMARYA simple and compact representation framework and the corresponding efficient numerical integration algorithm are developed for constitutive equations of isotropic elastoplasticity. Central to this work is the utilization of a set of mutually orthogonal unit tensor bases and the corresponding invariants. The set of bases can be regarded equivalently as a local cylindrical coordinate system in the three‐dimensional coaxial tensor subspace, namely, the principal space. The base tensors are given in the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Because of material isotropy, those response functions can be represented in terms of three isotropic invariants of their tensor arguments. Chen et al have shown that a convenient set of invariants is given by Haigh–Westergaard coordinates.…”
Section: Formulation In Haigh–westergaard Coordinatesmentioning
confidence: 99%
See 4 more Smart Citations
“…Because of material isotropy, those response functions can be represented in terms of three isotropic invariants of their tensor arguments. Chen et al have shown that a convenient set of invariants is given by Haigh–Westergaard coordinates.…”
Section: Formulation In Haigh–westergaard Coordinatesmentioning
confidence: 99%
“…Haigh–Westergaard coordinates of ϵ are defined by ξbold-italicϵ=I1,bold-italicϵ3,1emρbold-italicϵ=2J2,bold-italicϵ,1emθbold-italicϵ=13arccos()332J3,bold-italicϵJ2,bold-italicϵ3/2, where { I 1, ϵ , J 2, ϵ , J 3, ϵ } are the three usual isotropic invariants of ϵ : I1,bold-italicϵ=trbold-italicϵ,1emJ2,bold-italicϵ=12trbold-italice2,1emJ3,bold-italicϵ=13trbold-italice30.3em. In particular, ξ ϵ is the trace of ϵ divided by 3, ρ ϵ is the length of the deviatoric part of ϵ , and θ ϵ is the Lode angle. The trihedron constituted by the derivatives of the Haigh–Westergaard coordinates h ϵ ={ ξ ϵ , ρ ϵ , θ ϵ } with respect to the tensor ϵ (for instance, ), is then introduced: bold-italicf1,0.3embold-italicϵ=ξbold-italicϵbold-italicϵ,1embold-italicf2,0.3embold-italicϵ=ρbold-italicϵbold-italicϵ,1embold-italicf3,0.3embold-italicϵ=ρbold-italicϵθbold-italicϵbold-italicϵ0.3em. In Appendix A, classical form...…”
Section: Formulation In Haigh–westergaard Coordinatesmentioning
confidence: 99%
See 3 more Smart Citations